Interconnection technology for data center of telecom operator - Lili TANG; Ning ZHANG (Dianxin kexue)
With the continuous development of cloud computing and big data,service requirement to compute and storage challenges the scale of single data center.Building a data center interconnection network has become a must to achieve the data center scale up and service deployment flexibility.By constructing data center interconnection network,telecom operators can further integrate IT resource as“cloud”,in order to increase the resource utility and fasten new telecom service deployment efficiency,so to enhance the core business competitiveness.The representative solution of data center interconnection and the technology characteristic was analyzed.Combined with the requests of telecom resource integration,several data center interconnection technologies and their deployment in telecom carrier cloud network constructions were analyzed.